Disruption of Jmjd3/p16Ink4a Signaling Pathway Causes Bizarre Parosteal Osteochondromatous Proliferation (BPOP)‐like Lesion in Mice. (12th July 2021) - Zhang, Feng; Wang, Yingmei; Wang, Yuying; Wang, Xinli; Zhang, Dawei; Zhao, Xiong; Jiang, Runmin; Gu, Yu; Yang, Guifang; Fu, Xin; Xu, Longyong; Xu, Longxia; et al.
ABSTRACT: Bizarre parosteal osteochondromatous proliferation (BPOP), or Nora's lesion, is a rare benign osteochondromatous lesion. At present, the molecular etiology of BPOP remains unclear. JMJD3(KDM6B) is an H3K27me3 demethylase and counteracts polycomb‐mediated transcription repression. Previously, Jmjd3 was shown to be critical for bone development and osteoarthritis. Here, we report that conditional deletion of Jmjd3 in chondrogenic cells unexpectedly resulted in BPOP‐like lesion in mice. Biochemical investigations revealed that Jmjd3 inhibited BPOP‐like lesion through p16 Ink4a . Immunohistochemistry and RT‐qPCR assays indicated JMJD3 and p16 INK4A level were significantly reduced in human BPOP lesion compared with normal subjects. This was further confirmed by Jmjd3/Ink4a double‐gene knockout mice experiments. Therefore, our results indicated the pathway of Jmjd3/p16 Ink4a may be essential for the development of BPOP in human. © 2021 American Society for Bone and Mineral Research (ASBMR).